A basic model for cell cholesterol homeostasis. (19th October 2021) - Steck, Theodore L.; Tabei, S. M. Ali; Lange, Yvonne
Abstract: Cells manage their cholesterol by negative feedback using a battery of sterol‐responsive proteins. How these activities are coordinated so as to specify the abundance and distribution of the sterol is unclear. We present a simple mathematical model that addresses this question. It assumes that almost all of the cholesterol is associated with phospholipids in stoichiometric complexes. A small fraction of the sterol is uncomplexed and thermodynamically active. It equilibrates among the organelles, setting their sterol level according to the affinity of their phospholipids. The activity of the homeostatic proteins in the cytoplasmic membranes is then set by their fractional saturation with uncomplexed cholesterol in competition with the phospholipids. The high‐affinity phospholipids in the plasma membrane (PM) are filled to near stoichiometric equivalence, giving it most of the cell sterol. Notably, the affinity of the phospholipids in the endomembranes (EMs) is lower by orders of magnitude than that of the phospholipids in the PM. Thus, the small amount of sterol in the EMs rests far below stoichiometric capacity. Simulations match a variety of experimental data. The model captures the essence of cell cholesterol homeostasis, makes coherent a diverse set of experimental findings, provides a surprising prediction and suggests new experiments. Abstract : A mathematical model depicting how cells specify the level and distribution of their cholesterol is presented. Most cholesterol is in stoichiometric complexes with phospholipids. The small uncomplexed fraction distributes throughout the cell down its chemical activity gradient, tuning the activity of homeostatic proteins by negative feedback. The phospholipids in plasma membranes are avid for the sterol and filled nearly to capacity. Endomembrane cholesterol is held surprisingly weakly and rests far below the phospholipid capacity. Model simulations match experimental data.